UKURAN PERUSAHAAN SEBAGAI PEMODERASI PENGARUH KEPEMILIKAN PUBLIK KOMITE AUDIT DAN LABA RUGI TERHADAP AUDIT DELAY - Umi Arofah, Dewi Saptantinah Puji Astuti & Fadjar Harimurti (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2017)
This study aims to determine the influence of the public ownership, auditcomitte, and profit or loss. And to determine whether the size of the company’smoderate the relationship between the public ownership to the audit delay, auditcomittee to the audit delay, and profit or loss to the audit delay. This study uses dataanalysis techniques multiple regressions and with a total sample of 26 companies ofIndex LQ-45 listed on the Indonesian Stock Exchange with the observation period2013 to 2015. The result showed that the public ownership, audit comitte, and profitor loss do not influence towards audit delay. The size of the company is not able tomoderated the effect of public ownership on audit delay, audit comitte on auditdelay, and profit or loss to audit delay.Keywords: public ownership, , audit comitte, profit or loss,size of the company, auditdelay